In-situ polymerization dioxolane polymer solid electrolyte, magnesium fluoride-containing interface layer, battery and preparation method
Through the combination of in-situ polymerization of dioxolane composite polymer solid electrolyte and magnesium fluoride-containing interface layer, the problems of serious interface reaction and poor safety of traditional lithium-ion batteries are solved, and high energy density, long life and safer battery technology are achieved.
Patent Information
- Application Number
- CN202411802451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The capacity of traditional graphite negative electrodes has approached the theoretical limit. Liquid lithium-ion batteries have problems such as serious interface reactions and poor safety, which limits the further improvement of their energy density and safety.
In situ polymerized dioxolane composite polymer solid electrolyte is adopted, and inorganic-rich components containing magnesium fluoride are introduced into its interface layer. Through the competitive coordination between magnesium ions and lithium salt anions, the lithium ion coordination environment is regulated, the ionic conductivity of the electrolyte is improved, and a stable interface layer is formed at the interface of the positive and negative electrodes.
It significantly improves the ion conductivity and lithium ion migration number of the electrolyte, enhances the mechanical stability of the interface layer and lithium ion transport capacity, achieves uniform lithium deposition/peeling on the negative electrode side and excellent oxidation resistance on the positive electrode side, and improves the cycle stability and safety of the battery.
Smart Images

Figure CN119627208A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to battery technology, in particular to an in-situ polymerized dioxolane polymer solid electrolyte, a magnesium fluoride-containing interface layer, a battery and a preparation method thereof. Background Art
[0002] Since its introduction, lithium-ion batteries (LIBs) have been widely used in many fields such as consumer electronics, energy storage and new energy due to their many advantages such as low self-discharge, no memory effect, high energy density and long cycle life. With the increase in social demand, the new energy field has entered a new stage of development. Electric vehicles (EVs) are in urgent need of batteries with higher safety and longer endurance, so lithium-ion batteries are developing in the direction of high energy density, long life and greater safety. However, the capacity of traditional graphite negative electrodes is currently close to the theoretical limit, which limits the further improvement of the energy density of lithium batteries. Lithium metal and NCM811 have 3860mA·h·g –1 and more than 200mA·h·g –1 With high theoretical capacity, it is considered to be one of the most promising negative and positive electrode materials to achieve high energy density. However, the liquid lithium-ion batteries prepared by matching them with organic liquid electrolytes have many disadvantages such as severe interfacial reactions and poor safety, which limit their practical applications. For example, the growth of lithium dendrites leads to battery short circuit, thermal runaway and even explosion, and the serious side reactions between the electrolyte and the high-voltage positive electrode interface lead to rapid capacity decay. Solid-state lithium-ion batteries (ASSLBs) with high energy density and safety are theoretically the most promising alternatives to liquid lithium-ion batteries.
[0003] As one of the solid electrolytes, in-situ polymerized solid polymer electrolytes (SPEs) have the advantages of easy preparation, good electrode / electrolyte integration, and good interface contact, and are one of the most studied solid electrolytes. However, the existence of problems such as poor mechanical properties, severe lithium dendrite growth, and severe side reactions with high-voltage positive electrodes limits its practical use. For example, although the polydioxolane (PDOL) polymer-based solid electrolyte obtained by in-situ polymerization of dioxolane monomers (DOL) has good elastic plasticity and high ionic conductivity, it is difficult to inhibit the growth of lithium dendrites. At the same time, it is unstable to high-voltage positive electrodes and difficult to match high-voltage positive electrodes (such as high-nickel positive electrodes) for stable operation at high voltages. The existence of these problems leads to serious dendrite growth problems in batteries assembled with in-situ polymerized polymer solid electrolytes, serious side reactions on the positive electrode side, and difficulty in achieving stable operation. Therefore, it is imperative to construct a stable electrolyte / positive and negative electrode interface.
[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0005] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide an in-situ polymerized dioxolane polymer solid electrolyte, a magnesium fluoride-containing interface layer, a battery and a preparation method thereof.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing an in-situ polymerized dioxolane composite polymer solid electrolyte comprises: uniformly mixing 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction.
[0008] Further:
[0009] The support is selected from at least one of a PP membrane, a PE membrane, a PVDF (polyvinylidene fluoride) membrane, a PAN (polyacrylonitrile) membrane, a LATP (lithium aluminum titanium phosphate) electrospinning matrix, a LLZO (lithium lanthanum zirconium oxide) electrospinning matrix, and a BTO (barium titanate) electrospinning matrix.
[0010] The lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB), and lithium hexafluorophosphate (LiPF6).
[0011] A method for constructing an inorganic-rich interface layer containing magnesium fluoride comprises: uniformly mixing 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; and performing an electrochemical cycle, wherein magnesium ions and anions of the lithium salt react at the interface of the positive and negative electrodes to form an inorganic-rich interface layer containing magnesium fluoride.
[0012] An in-situ polymerized dioxolane composite polymer solid electrolyte is prepared using the in-situ polymerized dioxolane composite polymer solid electrolyte preparation method.
[0013] A magnesium fluoride-containing inorganic-rich interface layer is prepared using the method for constructing the magnesium fluoride-containing inorganic-rich interface layer.
[0014] A battery preparation method comprises: uniformly mixing 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; and performing an electrochemical cycle, wherein magnesium ions and anions of the lithium salt react at the interface of the positive and negative electrodes to form an inorganic component-rich interface layer containing magnesium fluoride.
[0015] A battery is prepared using the method for preparing a battery containing a magnesium fluoride-rich inorganic interface layer.
[0016] A battery comprises the in-situ polymerized solid electrolyte or the magnesium fluoride-containing inorganic rich interface layer.
[0017] A battery comprises a lithium metal negative electrode, a positive electrode, and a polymerized dioxolane composite polymer solid electrolyte formed on a support, wherein the polymerized dioxolane composite polymer solid electrolyte is formed by in-situ polymerization of 1,3-dioxolane monomers under the initiation of magnesium ions containing magnesium montmorillonite, and an inorganic component-rich interface layer containing magnesium fluoride is formed at the contact interface between the lithium metal negative electrode and / or the positive electrode and the polymerized dioxolane composite polymer solid electrolyte; preferably, the positive electrode is a high-nickel positive electrode.
[0018] The present invention has the following beneficial effects:
[0019] The invention provides an innovative in-situ polymerized dioxolane polymer solid electrolyte, a magnesium fluoride-containing interface layer, a battery and a preparation method thereof. The preparation method is to add magnesium-containing montmorillonite to dioxolane and lithium salt solutions, and use magnesium ions to initiate polymerization at room temperature to obtain a polydioxolane (PDOL) composite polymer solid electrolyte. The preparation process of this electrolyte is simple, the conditions are mild, the cost is low, and it has strong adaptability and universality. Due to the competitive coordination between magnesium ions and lithium salt anions, the lithium ion coordination environment inside the electrolyte is regulated, the number of free lithium ions is effectively increased, and the ionic conductivity of the electrolyte is significantly improved. In addition, the decomposition of magnesium ions and lithium salt anion ligands at the positive and negative electrode interfaces participates in the formation of the interface layer, and an inorganic component-rich interface layer (CEI and SEI) containing magnesium fluoride is produced. In addition to traditional inorganic components such as LiF, Li2CO3, Li2S and Li3N, this interface layer also specifically adds Mg2F magnesium-containing inorganic components. The introduction of magnesium fluoride, due to its high Young's modulus and low lithium ion transport barrier, greatly enhances the mechanical stability and lithium ion transport capacity of the interface layer, achieving uniform lithium deposition / stripping on the negative electrode side and excellent oxidation resistance stability on the positive electrode side. This composite polymer solid electrolyte exhibits a lithium ion transfer number of up to 0.60 and a wide electrochemical window of 5.3V. The Li / Li symmetric battery based on this electrolyte can be stably cycled for more than 6000 hours, while the Li / LiNi 0.8 Co 0.1 Mn 0.1 When used with O2 batteries, they exhibit excellent rate performance and cycle stability of more than 500 cycles, showing good application prospects in the battery field. Therefore, the present invention not only improves the performance of solid electrolytes, but also enhances the safety and cycle stability of batteries, which is of great significance for promoting the development of high energy density, long life and safer battery technology.
[0020] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Zeta potential test of montmorillonite in the embodiment of the present invention
[0022] Figure 2 This is the Zeta potential test of the montmorillonite in the examples of the present invention.
[0023] Figure 3 This is the Raman spectrum test of PDE and MPDE of the comparative examples and embodiments of the present invention.
[0024] Figure 4 This is the ionic conductivity test of PDE and MPDE of the comparative examples and embodiments of the present invention.
[0025] Figure 5 This is the electrochemical window LSV test of PDE and MPDE of the comparative examples and embodiments of the present invention.
[0026] Figure 6 This is the XPS composition analysis of the SEI on the lithium metal surface formed based on PDE and MPDE in the comparative examples and embodiments of the present invention.
[0027] Figure 7 This is the XPS composition analysis of the NCM811 surface CEI formed based on PDE and MPDE in the comparative examples and embodiments of the present invention.
[0028] Figure 8 This is a comparison chart of Young's modulus of SEI and CEI of the interface layers formed based on PDE and MPDE in the comparative examples and embodiments of the present invention.
[0029] Fig. 9 The lithium ion migration barrier of lithium fluoride and magnesium fluoride in the comparative examples and embodiments of the present invention.
[0030] Fig.10 The long cycle performance of the symmetrical battery based on PDE and MPDE in-situ polymerized lithium in the comparative examples and embodiments of the present invention.
[0031] Fig.11 It is the rate performance test curve of the full battery based on PDE and MPDE in-situ polymerization of the comparative examples and embodiments of the present invention.
[0032] Fig.12 It is the long cycle performance test curve of the full battery based on PDE and MPDE in-situ polymerization of the comparative examples and embodiments of the present invention. DETAILED DESCRIPTION
[0033] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0034] According to an embodiment of the present invention, a method for preparing an in-situ polymerized dioxolane composite polymer solid electrolyte comprises: uniformly mixing 1,3-dioxolane, 1 to 4 M lithium salt and 2 to 15 wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction.
[0035] A method for constructing an inorganic-rich interface layer containing magnesium fluoride comprises: uniformly mixing 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; and performing an electrochemical cycle, wherein magnesium ions and anions of the lithium salt react at the interface of the positive and negative electrodes to form an inorganic-rich interface layer containing magnesium fluoride.
[0036] A battery preparation method comprises: uniformly mixing 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite to obtain a mixed solution, then immersing the mixed solution in a support, matching with a lithium metal negative electrode and a positive electrode to assemble a full battery, standing for a period of time, and obtaining a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; and performing an electrochemical cycle, wherein magnesium ions and anions of the lithium salt react at the interface of the positive and negative electrodes to form an inorganic component-rich interface layer containing magnesium fluoride.
[0037] The embodiments of the present invention also provide an in-situ polymerized dioxolane composite polymer solid electrolyte, a magnesium fluoride-containing inorganic rich interface layer and a battery prepared by the above method.
[0038] The battery comprises a lithium metal negative electrode, a positive electrode, and a polymerized dioxolane composite polymer solid electrolyte formed on a support, wherein the polymerized dioxolane composite polymer solid electrolyte is formed by in-situ polymerization of 1,3-dioxolane monomers under the initiation of magnesium ions in magnesium-containing montmorillonite, and a layer of inorganic component-rich interface layer containing magnesium fluoride is formed at the contact interface between the lithium metal negative electrode and / or the positive electrode and the polymerized dioxolane composite polymer solid electrolyte. Preferably, the positive electrode is a high-nickel positive electrode.
[0039] Among them, the mechanism and process of in-situ polymerization of DOL initiated by magnesium ions are shown in formula (I):
[0040]
[0041] The in-situ polymerized solid electrolyte and solid-state battery properties are as follows Figure 1 shown.
[0042] According to some embodiments of the present invention, the dioxolane, the lithium salt and the magnesium-containing montmorillonite are mixed in a certain proportion to obtain a mixed solution, an appropriate amount of the mixed solution is dropped onto a support, and the mixture is allowed to stand for a period of time at room temperature to undergo in-situ polymerization to obtain a composite polymer solid electrolyte; the obtained solid electrolyte is matched with a lithium metal negative electrode and a high-voltage positive electrode, and in-situ chemical and electrochemical reactions occur during physical contact and electrochemical charge and discharge to generate an inorganic component-rich interface layer containing magnesium fluoride.
[0043] In an embodiment of the present invention, magnesium-containing montmorillonite is added to a dioxolane (DOL) and lithium salt solution, and magnesium ions initiate in-situ polymerization at room temperature to obtain a polydioxolane (PDOL) composite polymer solid electrolyte. Magnesium ions spontaneously aggregated on the surface of montmorillonite compete with lithium salt anions for coordination, regulate the lithium ion coordination environment inside the electrolyte, increase the number of free lithium ions, and thus improve the ionic conductivity of the electrolyte. In addition, magnesium ions and lithium salt anion ligands decompose at the positive and negative electrode interfaces to participate in the formation of the interface layer, producing an inorganic component-rich interface layer (CEI and SEI) containing magnesium fluoride. The magnesium fluoride-containing inorganic interface layer has a high Young's modulus and fast lithium ion transport kinetics, which is conducive to the rapid transport of lithium ions and improves the stability of the electrolyte and the positive and negative electrode interfaces. The composite polymer solid electrolyte exhibits a lithium ion migration number of up to 0.60 and a wide electrochemical window of 5.3V. The Li / Li symmetric battery based on the composite polymer solid electrolyte can stably cycle for more than 6000 hours, and the Li / LiNi 0.8 Co 0.1 Mn 0.1 O2 batteries show excellent rate performance and cycle stability of more than 500 cycles, and have good application prospects in the battery field.
[0044] In some embodiments, the support may be selected from PP membrane, PE membrane, PVDF (polyvinylidene fluoride) membrane, PAN (polyacrylonitrile) membrane, LATP (lithium aluminum titanium phosphate) electrospinning matrix, LLZO (lithium lanthanum zirconium oxide) electrospinning matrix, BTO (barium titanate) electrospinning matrix. The lithium salt may be selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB), lithium hexafluorophosphate (LiPF6).
[0045] The in-situ polymerized composite solid electrolyte provided by the present application comprises polydioxolane, a support, a lithium salt and magnesium-containing montmorillonite, has uniform polymer segment distribution, high ionic conductivity, high lithium ion migration number (0.60), high mechanical strength and wide electrochemical window (5.3V), can well match the lithium metal negative electrode and the NCM811 positive electrode, and has great application value. The preparation method provided by the present application is simple, the in-situ reaction conditions are mild, the cost is low, and it has strong adaptability and universality. The prepared composite solid electrolyte and the interface layer containing magnesium fluoride-rich inorganic components can be applied to lithium metal / high nickel ternary batteries to improve the stability of the solid electrolyte to lithium metal and high-voltage positive electrodes.
[0046] The specific embodiments of the present invention are further described below.
[0047] A magnesium ion-initiated dioxolane in-situ polymerization polymer solid electrolyte, a magnesium fluoride-containing interface layer, a battery and a preparation method thereof.
[0048] Example 1
[0049] This embodiment provides a composite solid electrolyte (MPDE composite solid electrolyte), which is prepared according to the following steps:
[0050] Step S1, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, and stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution.
[0051] Step S2, adding 100 mg of montmorillonite to the transparent solution obtained in step S1, stirring at room temperature for more than 10 minutes to obtain a mixed solution.
[0052] Step S3, adding the mixed solution obtained in step S2 dropwise onto the PP diaphragm, placing it in a glove box and standing at room temperature for 24 hours, in-situ polymerizing to obtain the MPDE composite solid electrolyte membrane, punching it into a suitable size, and storing it dry in an inert atmosphere for future use.
[0053] Comparative Example 1
[0054] This comparative example provides an in-situ polymerized solid electrolyte (PDE composite solid electrolyte), which is prepared according to the following steps:
[0055] Step S1, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, and stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution.
[0056] Step S2, add 100 mg of LiPF6 (lithium hexafluorophosphate) to the transparent solution obtained in step S1, and stir at room temperature for more than 10 minutes to obtain a uniform solution.
[0057] Step S3, dripping the solution obtained in step S2 onto the PP diaphragm, placing it in a glove box and standing at room temperature for 24 hours, in-situ polymerizing to obtain a PDE solid electrolyte membrane, punching it into a suitable size, and storing it dry in an inert atmosphere for future use.
[0058] Figure 2 This is the Zeta potential test of montmorillonite. The result is positive, indicating that magnesium ions spontaneously gather on the surface of montmorillonite and the whole is positively charged.
[0059] Figure 3Raman spectra of PDE and MPDE. The Raman shift of the MPDE sample corresponding to the TFSI anion shifts to high wavenumbers, proving that there is a competitive coordination effect between the magnesium ions of montmorillonite and the TFSI anions.
[0060] Figure 4 This is the ion conductivity test of PDE and MPDE. In MPDE, magnesium ions compete with lithium salt anions to produce more free lithium ions, and the ion conductivity increases.
[0061] Figure 5 LSV test of electrochemical window of PDE and MPDE. MPDE shows a wider electrochemical window of 5.3V.
[0062] Example 2
[0063] This embodiment provides an assembled battery and an inorganic interface layer containing magnesium fluoride, which are assembled according to the following steps:
[0064] Step S1, prepare positive electrode slurry: first weigh 100 mg PVDF (binder) and place it in a stirring bottle, add 1 mL NMP (N-methylpyrrolidone), and stir on a small stirrer for 1 hour until PVDF is completely dissolved. Then add 100 mg SuperP (conductive carbon black) and 1 mL NMP, stir at room temperature for 1 hour, add 800 mg NCM811 (ternary material nickel cobalt manganese) active material and 1.5 mL NMP, and stir at room temperature for more than 6 hours.
[0065] Step S2, preparing the positive electrode: coating the positive electrode slurry obtained in step S1 on aluminum foil, drying at 80° C. for more than 6 h, cutting into a suitable size to obtain an NCM811 positive electrode, and placing in a vacuum oven for drying and storage.
[0066] Step S3: First, weigh 2583 mg of LiTFSI (bis(trifluoromethylsulfonyl)sulfonyl) in an inert atmosphere. 144 mg of LiDFOB (lithium difluorooxalate borate) was placed in a stirring bottle, and 5 mL of DOL (1,3-dioxolane) was added, and stirred on a small stirrer, and stirred at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution. 100 mg of montmorillonite was added to the transparent solution obtained in step S1, and stirred at room temperature for more than 10 minutes to obtain a mixed solution.
[0067] Step S4, according to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the PP separator, the mixed solution obtained in step S3 and lithium metal are assembled into a full battery. The full battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid MPDE full battery. The full battery is charged and discharged for 3 times at a current density of 0.1C to construct an inorganic interface layer containing magnesium fluoride at the interface between the positive and negative electrodes.
[0068] According to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the PP separator, the mixed solution obtained in step S2 of comparative example 1 and lithium metal were assembled into a full battery. The full battery was left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state PDE full battery. The full battery was charged and discharged for 3 times at a current density of 0.1C to construct a common interface layer at the interface between the positive and negative electrodes.
[0069] Step S5, according to the symmetric battery assembly process, the PP separator and the mixed solution obtained in step S3 are sandwiched between two layers of lithium metal to assemble into a lithium-lithium symmetric battery. The symmetric battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid MPDE symmetric battery. The symmetric battery is heated at 0.1 mA / cm 2 、0.1mAh / cm 2 The reaction was cycled 30 times to construct an inorganic SEI containing magnesium fluoride-rich lithium metal anode.
[0070] According to the symmetric battery assembly process, the PP separator and the mixed solution obtained in step S2 of comparative example 1 were sandwiched between two layers of lithium metal to assemble a lithium-lithium symmetric battery. The symmetric battery was left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state PDE symmetric battery. The symmetric battery was heated at 0.1 mA / cm 2 , 0.1mA h / cm 2 After 30 cycles, a lithium metal negative electrode containing a common SEI was constructed.
[0071] Figure 6 XPS composition analysis of SEI on lithium metal surface formed by PDE and MPDE. Figure 7 This is the XPS composition analysis of CEI on the surface of NCM811 formed based on PDE and MPDE. It can be found that the interface layer based on MPDE has less CO organic components than that based on PDE, proving that the interface decomposition of MPDE electrolyte is reduced. In addition, the interface layer formed by MPDE contains a new component of magnesium fluoride, which is beneficial to improve the mechanical strength and lithium ion transport capacity of the interface layer, and improve the protective effect of the interface layer on the positive and negative electrodes.
[0072] Figure 8 The Young's modulus comparison chart of the interfacial layers SEI and CEI formed based on PDE and MPDE. The results show that magnesium fluoride has a higher Young's modulus than lithium fluoride. Due to the presence of magnesium fluoride, the Young's modulus of SEI and CEI formed based on MPDE electrolyte are greatly improved.
[0073] Fig. 9 The results show that magnesium fluoride has a lower lithium ion migration barrier than the traditional component lithium fluoride, which is beneficial to the transport of lithium ions in the magnesium fluoride-containing interface layer.
[0074] Fig.10 The long cycle performance of the symmetrical lithium battery based on in-situ polymerization of PDE and MPDE is shown in Figure 2. The results show that at room temperature and a current density of 0.1 mA cm –2 , surface capacity is 0.1 mAh cm –2 Under these conditions, the Li / MPDE / Li battery can be stably cycled for more than 6000 hours and exhibits a low overpotential. In contrast, the symmetric PDE-based battery has a high overpotential and a short cycle life, which shows the advanced nature of the magnesium fluoride-containing interface layer.
[0075] Fig.11 This is the rate performance test curve of the full battery based on the in-situ polymerization of PDE and MPDE. As can be seen from the figure, the full battery assembled after MPDE matches the NCM811 positive electrode and the lithium metal negative electrode shows excellent rate performance and can still exert a capacity of 128mAh / g at a current density of 0.5C at room temperature.
[0076] Fig.12 This is a long cycle performance test curve of the full battery based on the in-situ polymerization of PDE and MPDE. As can be seen from the figure, the full battery assembled after MPDE matches the NCM811 positive electrode and the lithium metal negative electrode shows excellent cycle stability performance, and can stably cycle 500 times at room temperature 0.1C, with a capacity retention rate of 82.6%.
[0077] Example 3
[0078] This embodiment provides an assembled battery, which is assembled according to the following steps:
[0079] Step S1, prepare positive electrode slurry: first weigh 100 mg PVDF (binder) and place it in a stirring bottle, add 1 mL NMP (N-methylpyrrolidone), and stir on a small stirrer for 1 hour until PVDF is completely dissolved. Then add 100 mg SuperP (conductive carbon black) and 1 mL NMP, stir at room temperature for 1 hour, add 800 mg NCM811 (ternary material nickel cobalt manganese) active material and 1.5 mL NMP, and stir at room temperature for more than 6 hours.
[0080] Step S2, preparing the positive electrode: coating the positive electrode slurry obtained in step S1 on aluminum foil, drying at 80° C. for more than 6 h, cutting into a suitable size to obtain an NCM811 positive electrode, and placing in a vacuum oven for drying and storage.
[0081] Step S3, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution. Take 100 mg of montmorillonite and add it to the transparent solution obtained in step S1, stir at room temperature for more than 10 minutes to obtain a mixed solution.
[0082] Step S4, according to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the PE separator, the mixed solution obtained in step S3 and lithium metal are assembled into a full battery. The full battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state full battery.
[0083] Example 4
[0084] This embodiment provides an assembled battery, which is assembled according to the following steps:
[0085] Step S1, prepare positive electrode slurry: first weigh 100 mg PVDF (binder) and place it in a stirring bottle, add 1 mL NMP (N-methylpyrrolidone), and stir on a small stirrer for 1 hour until PVDF is completely dissolved. Then add 100 mg SuperP (conductive carbon black) and 1 mL NMP, stir at room temperature for 1 hour, add 800 mg NCM811 (ternary material nickel cobalt manganese) active material and 1.5 mL NMP, and stir at room temperature for more than 6 hours.
[0086] Step S2, preparing the positive electrode: coating the positive electrode slurry obtained in step S1 on aluminum foil, drying at 80° C. for more than 6 h, cutting into a suitable size to obtain an NCM811 positive electrode, and placing in a vacuum oven for drying and storage.
[0087] Step S3, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution. Take 100 mg of montmorillonite and add it to the transparent solution obtained in step S1, stir at room temperature for more than 10 minutes to obtain a mixed solution.
[0088] Step S4, according to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the PVDF separator, the mixed solution obtained in step S3 and lithium metal are assembled into a full battery. The full battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state full battery.
[0089] Example 5
[0090] This embodiment provides an assembled battery, which is assembled according to the following steps:
[0091] Step S1, prepare positive electrode slurry: first weigh 100 mg PVDF (binder) and place it in a stirring bottle, add 1 mL NMP (N-methylpyrrolidone), and stir on a small stirrer for 1 hour until PVDF is completely dissolved. Then add 100 mg SuperP (conductive carbon black) and 1 mL NMP, stir at room temperature for 1 hour, add 800 mg NCM811 (ternary material nickel cobalt manganese) active material and 1.5 mL NMP, and stir at room temperature for more than 6 hours.
[0092] Step S2, preparing the positive electrode: coating the positive electrode slurry obtained in step S1 on aluminum foil, drying at 80° C. for more than 6 h, cutting into a suitable size to obtain an NCM811 positive electrode, and placing in a vacuum oven for drying and storage.
[0093] Step S3, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution. Take 100 mg of montmorillonite and add it to the transparent solution obtained in step S1, stir at room temperature for more than 10 minutes to obtain a mixed solution.
[0094] Step S4, according to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the LLZTO support, the mixed solution obtained in step S3 and lithium metal are assembled into a full battery. The full battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state full battery.
[0095] Example 6
[0096] This embodiment provides an assembled battery, which is assembled according to the following steps:
[0097] Step S1, prepare positive electrode slurry: first weigh 100 mg PVDF (binder) and place it in a stirring bottle, add 1 mL NMP (N-methylpyrrolidone), and stir on a small stirrer for 1 hour until PVDF is completely dissolved. Then add 100 mg SuperP (conductive carbon black) and 1 mL NMP, stir at room temperature for 1 hour, add 800 mg NCM811 (ternary material nickel cobalt manganese) active material and 1.5 mL NMP, and stir at room temperature for more than 6 hours.
[0098] Step S2, preparing the positive electrode: coating the positive electrode slurry obtained in step S1 on aluminum foil, drying at 80° C. for more than 6 h, cutting into a suitable size to obtain an NCM811 positive electrode, and placing in a vacuum oven for drying and storage.
[0099] Step S3, first weigh 2583 mg of LiTFSI (lithium bis(trifluoromethylsulfonyl)imide) and 144 mg of LiDFOB (lithium difluorooxalatoborate) in an inert atmosphere and place them in a stirring bottle, add 5 mL of DOL (1,3-dioxolane), stir on a small stirrer, stir at room temperature for more than 10 minutes to completely dissolve to obtain a uniform transparent solution. Take 100 mg of montmorillonite and add it to the transparent solution obtained in step S1, stir at room temperature for more than 10 minutes to obtain a mixed solution.
[0100] Step S4, according to the full battery assembly process, the NCM811 positive electrode prepared in step S2, the BTO support, the mixed solution obtained in step S3 and lithium metal are assembled into a full battery. The full battery is left to stand at room temperature for 24 hours to obtain an in-situ polymerized solid-state full battery.
[0101] In summary, the present invention proposes an in-situ polymerized dioxolane polymer solid electrolyte, a magnesium fluoride-containing interface layer, a battery and a preparation method thereof. By adding magnesium-containing montmorillonite to dioxolane (DOL) and a lithium salt solution, an in-situ polymerization reaction is initiated by magnesium ions at room temperature, and a polydioxolane (PDOL) composite polymer solid electrolyte is successfully prepared. This process is not only simple, but also has mild in-situ reaction conditions, low cost, and strong adaptability and universality, so that the prepared composite solid electrolyte and the interface layer containing magnesium fluoride-rich inorganic components can be widely used in lithium metal / high nickel ternary batteries, thereby improving the stability of the solid electrolyte to lithium metal and high-voltage positive electrodes.
[0102] In the electrolyte, the magnesium ions spontaneously gathered on the surface of montmorillonite compete with the lithium salt anions for coordination, effectively regulating the lithium ion coordination environment, increasing the number of free lithium ions, and thus improving the ionic conductivity of the electrolyte. The solution participates in the formation of the interface layer, producing a magnesium fluoride-rich Inorganic component interface layer (CEI and SEI) This magnesium fluoride-containing inorganic rich interface layer exhibits high Young's modulus and fast lithium ion transport kinetic properties, which is conducive to the rapid transport of lithium ions and improves the stability of the electrolyte and positive and negative electrode interfaces.
[0103] The composite polymer solid electrolyte has a lithium ion transference number of up to 0.60 and a wide electrochemical window of 5.3V, which enables the Li / Li symmetric battery based on this electrolyte to be stably cycled for more than 6000 hours, compared with Li / LiNi 0.8 Co 0.1 Mn 0.1 When used in combination with O2 batteries, they exhibit excellent rate performance and cycle stability of more than 500 cycles, showing good application prospects in the battery field.
[0104] The interface layer prepared by the present invention is a SEI / CEI containing magnesium fluoride-rich inorganic components on the surface of a lithium metal negative electrode / high nickel positive electrode, which not only contains traditional inorganic components such as LiF, Li2CO3, Li2S and Li3N, but also contains Mg2F magnesium-containing inorganic components. The introduction of magnesium fluoride, due to its high Young's modulus and low lithium ion transport barrier, greatly enhances the mechanical stability and lithium ion transport capacity of the interface layer, achieves uniform lithium deposition / stripping on the negative electrode side and excellent oxidation resistance stability on the positive electrode side. Therefore, the composite solid electrolyte based on the interface layer containing magnesium fluoride-rich inorganic components matches the lithium metal negative electrode and exhibits long cycle stability, and the lithium-lithium symmetric battery can stably cycle for more than 6000 hours. The full battery formed by matching and assembling with the lithium metal negative electrode and the NCM811 positive electrode exhibits excellent rate and cycle performance at room temperature, further proving that it has good application prospects in the field of batteries.
[0105] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing an in-situ polymerized dioxolane composite polymer solid electrolyte, characterized in that: include: 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite are uniformly mixed to obtain a mixed solution, which is then immersed in a support, matched with a lithium metal negative electrode and a positive electrode to assemble into a full battery, and allowed to stand for a period of time to obtain a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction.
2. The method for preparing the in-situ polymerized dioxolane composite polymer solid electrolyte according to claim 1, characterized in that: The support is selected from at least one of a PP membrane, a PE membrane, a PVDF (polyvinylidene fluoride) membrane, a PAN (polyacrylonitrile) membrane, a LATP (lithium aluminum titanium phosphate) electrospinning matrix, a LLZO (lithium lanthanum zirconium oxide) electrospinning matrix, and a BTO (barium titanate) electrospinning matrix.
3. The method for preparing the in-situ polymerized dioxolane composite polymer solid electrolyte according to claim 1 or 2, characterized in that: The lithium salt is selected from at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiDFOB), and lithium hexafluorophosphate (LiPF6).
4. A method for constructing an inorganic-rich interface layer containing magnesium fluoride, characterized in that: include: 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite are uniformly mixed to obtain a mixed solution, and then the mixed solution is immersed in a support body, matched with a lithium metal negative electrode and a positive electrode to assemble a full battery, and allowed to stand for a period of time to obtain a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; an electrochemical cycle is performed, and magnesium ions and lithium salt anions react at the interface of the positive and negative electrodes to form an inorganic component-rich interface layer containing magnesium fluoride.
5. An in-situ polymerized dioxolane composite polymer solid electrolyte, characterized in that: The solid electrolyte is prepared by the method for preparing the in-situ polymerized dioxolane composite polymer solid electrolyte as claimed in claim 1.
6. A magnesium fluoride-containing inorganic rich interface layer, characterized in that: The method for constructing a magnesium fluoride-containing inorganic-rich interface layer as described in claim 4 is used to prepare the layer.
7. A method for preparing a battery, characterized in that: include: 1,3-dioxolane, 1-4M lithium salt and 2-15wt.% magnesium-containing montmorillonite are uniformly mixed to obtain a mixed solution, and then the mixed solution is immersed in a support body, matched with a lithium metal negative electrode and a positive electrode to assemble a full battery, and allowed to stand for a period of time to obtain a polymerized dioxolane composite polymer solid electrolyte through an in-situ polymerization reaction; an electrochemical cycle is performed, and magnesium ions and lithium salt anions react at the interface of the positive and negative electrodes to form an inorganic component-rich interface layer containing magnesium fluoride.
8. A battery, characterized in that: The battery is prepared using the method for preparing a battery containing a magnesium fluoride-rich inorganic interface layer as described in claim 7.
9. A battery, characterized in that: It comprises the in-situ polymerized solid electrolyte as claimed in claim 5, or the magnesium fluoride-containing inorganic rich interface layer as claimed in claim 6.
10. A battery, characterized in that: The invention comprises a lithium metal negative electrode, a positive electrode, and a polymerized dioxolane composite polymer solid electrolyte formed on a support, wherein the polymerized dioxolane composite polymer solid electrolyte is formed by in-situ polymerization of 1,3-dioxolane monomer under the initiation of magnesium ions of magnesium-containing montmorillonite, and an inorganic component-rich interface layer containing magnesium fluoride is formed at the contact interface between the lithium metal negative electrode and / or the positive electrode and the polymerized dioxolane composite polymer solid electrolyte; preferably, the positive electrode is a high-nickel positive electrode.
Citation Information
Patent Citations
Battery, electrolyte, battery pack, electronic apparatus, electric vehicle, electricity storage device, and power system
CN105684205A
PVDF (Polyvinylidene Fluoride)-based composite solid electrolyte as well as preparation method and application thereof
CN118610573A
Negative electrode mixture or GEL electrolyte, and battery using said negative electrode mixture or said GEL electrolyte
US20140205909A1
Cited By
High-voltage chloride solid electrolyte with stable in-situ polyacrylonitrile flexible ion transmission interface layer and preparation method and application of high-voltage chloride solid electrolyte
CN121123378A